2017
DOI: 10.15537/smj.2017.11.20479
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of preoperative serum cancer antigen 15-3 levels in endometrial carcinomas

Abstract: Objectives:To determine the associations between serum cancer antigen 15-3 levels and prognostic factors in patients with endometrial carcinomas. Additionally, we investigated the clinical utility of serum cancer antigen 15-3 levels in the selection of low-risk patients with endometrioid type, tumor size <2 cm, myometrial invasion ≤50%, and histological grade 1-2.Methods:Ninety-six patients, who were surgically staged at Ankara Yildirim Beyazit University, Ankara, Turkey, between 2007 and 2016, were retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…CA15.3 levels significantly correlated with prognostic factors and were a useful prognostic tool for endometrial (uterine) cancer (55) . However, whether equol impacts the initiation and development of endometrial cancer by affecting the level of CA15.3 needs further research verification.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…CA15.3 levels significantly correlated with prognostic factors and were a useful prognostic tool for endometrial (uterine) cancer (55) . However, whether equol impacts the initiation and development of endometrial cancer by affecting the level of CA15.3 needs further research verification.…”
Section: Discussionmentioning
confidence: 98%
“…We further analysed the correlation between CA15.3 and urinary equol in twenty-four HRC patients by cancer type and found that there was a discrepant correlation in the various cancers (for breast cancer: n 16, r = 0·420, P = 0·119; for uterine cancer: n 7, r = 0·843; P = 0·035; data not shown). Studies have suggested that CA15.3 levels significantly correlated with prognostic factors and were a useful prognostic tool for endometrial (uterine) cancer (55) . However, whether equol impacts the initiation and development of endometrial cancer by affecting the level of CA15.3 needs further research verification.…”
Section: Discussionmentioning
confidence: 99%
“…In studies evaluating risk factors for LN metastasis in patients with EC, the parameters that are considered as negative prognostic factors for EC are also indicated as risk factors for LN metastasis (6)(7)(8)(14)(15)(16). However, there is no consistency between the results of similar studies.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no definite method to detect the presence of LN metastases preoperatively or intraoperatively (6)(7)(8)(9)(10)(11). For this reason, FIGO and "American Congress of Obstetricians and Gynecologists" recommend performing both pelvic and paraaortic LN sampling in surgical staging of patients with EC (12).…”
Section: Introductionmentioning
confidence: 99%
“…The reduced hospital stay in TLH patients indicates lower cost and rapid recovery. (29) 1988 28 (31) 17 (11) Zorlu et al (30) 1994 2 ( 7) 1 (4) Larson et al (27) 1995 9 (24) 5 ( 14) Frumovitz et al (28) 2004 23 ( 27) 19 ( 23) Stephan et al (31) 2014 24 ( 29 Serum markers such as CA-125, CA-15-3, and CA-19-9 may be a useful to predict endometrial cancer preoperatively (40,41) . Panidis et al (6) reported that mean serum CA-125, CA-15-3, and CA-19-9 values were 56.8, 43.1, and 30.1, respectively.…”
Section: Discussionmentioning
confidence: 99%